2022
DOI: 10.55927/eajmr.v1i9.1261
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Effects of Flooding in Nigeria: A Review

Abstract: Flooding is an environmental hazard that needs appropriate measures to be instituted to stem the tide of occurrence. The study relied on previous academic/scholarly articles in achieving the aim.  It was noted in the study that flooding is caused by natural and human activities. For instance, excessive rainfall, terrain and nature of soils are natural causes of flooding. Furthermore, poor environmental planning/monitoring, housing development in flood prone areas, deforestation, haphazard developments resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Causes of flood in Nigeria are generally divided into three factors (i) meteorological factors: oceans storms and tidal waves usually along the coastal areas, heavy rainstorms; (ii) physical factors: insufficient drainage management, and catchment area; (iii) human factors: poor land use planning; siltation, deforestation, collapse of dams, lack of flood management policies, and institutional arrangements etc., [10,19,51,[57][58][59]. Nwigwe and Emberga [57] observed that in Nigeria flood occurs either in forms coastal flood, rriver flooding, flash floods, uurban flooding, fluvial flood, dam burst leave failures, and dam spills.…”
Section: What Are the Most Common Causes Of Flood In Nigeria?mentioning
confidence: 99%
See 3 more Smart Citations
“…Causes of flood in Nigeria are generally divided into three factors (i) meteorological factors: oceans storms and tidal waves usually along the coastal areas, heavy rainstorms; (ii) physical factors: insufficient drainage management, and catchment area; (iii) human factors: poor land use planning; siltation, deforestation, collapse of dams, lack of flood management policies, and institutional arrangements etc., [10,19,51,[57][58][59]. Nwigwe and Emberga [57] observed that in Nigeria flood occurs either in forms coastal flood, rriver flooding, flash floods, uurban flooding, fluvial flood, dam burst leave failures, and dam spills.…”
Section: What Are the Most Common Causes Of Flood In Nigeria?mentioning
confidence: 99%
“…Flood risk is the product of the flood hazards probability, the vulnerability and the exposure of the environment, people and the economy [35]. As highlighted by various studies flood risk probability is high in Nigeria, every region is vulnerable to flood [19,35,64]. In terms of climate change, Nigeria ranks as the 7th most vulnerable country in the world because the country is located in one of the most vulnerable regions in the world (Verisk Maplecroft's Climate Change Vulnerability Index 2016) [65].…”
Section: An Overview Of Flood Risk Exposure and Vulnerability In Nigeriamentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar view Ujene and Oguike (2020) reveled that flooding causes inundation and harm to plants and animals, including man, buildings and infrastructure, Meanwhile, in the year 2022, flood damages in Nigeria affected over 2.5 million people, with over 600 people killed and another 2,400 injured (Oguntola 2022). Ifiok et al (2022) pointed out that that flooding is caused by natural and human activities. For instance, excessive rainfall, terrain and nature of soils are natural causes of flooding.…”
Section: Introductionmentioning
confidence: 99%